Formulation and Evaluation of Phytosome for the Topical Drug Delivery - Mandwe S. Vrushabh,; Dr. Sandeep C. Atram,; Bhonde G. Akash,; Bawankar V. Dipali,; Puri G. Ashutosh, (Asian Journal of Pharmaceutical Research and Development, 2025)
The aim of the present study was formulation and evaluation of phytosome for the topical drug delivery. Quercetin loaded phytosome were prepared by ether injection method. The prepared phytosome were further characterized for particle size, zeta potential, entrapment efficiency, drug content and in-vitro diffusion study.On the basis of criteria (the drug diffused at 4 Hr. not more than 20%, not less than 15%) the F2 batch is optimized and the optimized batch is incorporated in gel for further evaluation such as pH determination, drug content, viscosity and in-vitro diffusion study. From the in-vitro diffusion study we observed that the quercetin release from phytosomal gel by zero order kinetics which show controlled release of quercetin from phytosomal gel.